Radiocarbon dating, grain size analyses, and XRF data on sediments from the Hauraki Gulf, New Zealand - Dierk Hebbeln; Florian Boxberg (PANGAEA, 2019)
Based on the analysis of 14 short sediment cores, we present new insights into the distribution of surficial sediments in the central Hauraki Gulf, a semi-enclosed coastal embayment on the northeast coast of New Zealand extquotesingles North Island. We identify and discuss the effects of interaction of modern wind-generated waves and currents with regard to deposition and reworking of sediments in the Gulf. The modern hydrodynamic regime is controlled by tidal currents, oceanic inflows, and wave-induced currents and it is responsible for a N-S gradient in sediment texture and elemental concentrations in the central Hauraki Gulf sediments. The present-day sediment input into the system is generally low and consists of fine-grained fluvial sediments mostly deposited in the southern study area and comparatively high inputs of relict carbonate material to the northern study sites. The central Hauraki Gulf sediments, which show numerous age reversals in the sedimentary record, can be characterised as palimpsest sediments, as a consequence of continuous reworking and storm-induced sediment transport. In view of the new data, a previously assumed significant post-transgression accumulation of sediments of >0.167em10 m in the central Hauraki Gulf appears to be very unlikely.
Supplement to: Boxberg, Florian; Blossier, Brice; de Lange, Willem P; Fox, Bethany R Storrs; Hebbeln, Dierk (2020): Sediment deposition in the central Hauraki Gulf, New Zealand. Geo-Marine Letters, 40(2), 227-241, https://doi.org/10.1007/s00367-019-00583-1